The quantity theory of money. Reply to Dr. R.S. Masera - KELLY, A. (PSL Quarterly Review, 2014)
In this brief note, the author responds to R.S. Masera’s criticism of the author’s position on the quantity theory of money. The author maintains that the monetary authorities cannot arbitrarily create excessive money balances in the hands of the public and that as a consequence monetary policy is likely to be ineffective and possibly even disruptive. JEL: B22, E41, E51, E52